2020
DOI: 10.1167/iovs.61.6.21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Contrast Sensitivity Measured Using Quick Contrast Sensitivity Function With Other Visual Functions in a Low Vision Population

Abstract: Relationship of contrast sensitivity measured using quick contrast sensitivity function with other visual functions in a low vision population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Besides BCVA and fine stereopsis, CSF is also a nonnegligible clinical parameter. CSF is the ability to differentiate luminance variations between adjacent areas and offers a more complete assessment of spatial vision, which is more representative in performing everyday visual tasks, such as driving and perceiving faces [ 43 ]. It is generally believed that the CSF of amblyopic eyes declines, especially in moderate and high spatial frequencies [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides BCVA and fine stereopsis, CSF is also a nonnegligible clinical parameter. CSF is the ability to differentiate luminance variations between adjacent areas and offers a more complete assessment of spatial vision, which is more representative in performing everyday visual tasks, such as driving and perceiving faces [ 43 ]. It is generally believed that the CSF of amblyopic eyes declines, especially in moderate and high spatial frequencies [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our daily life, relative motion can be constantly observed between observers and objects. Dynamic visual acuity (DVA) defines the ability to identify the details of an object with relative motion (Ao et al, 2014; Ren et al, 2020; Stalin & Dalton, 2020; Wu et al, 2021). DVA is crucial for driving and in sports performance, including baseball, (Uchida et al, 2013) volleyball (Hoshina et al, 2013) and motor sports (Schneiders et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a correlation between CSF and VA in a population with low VA population. [21] However, no significant correlation between CSF and VA was reported in a population with normal VA. [22] A possible explanation for the lack of significant differences in the analysis of interocular differences in CS with respect to interocular spherical refraction may be the concentrated CDVA distribution in the patients of this study and its good performance at low spatial frequencies, as mild retinal changes although not significant may have occurred, while significant retinal changes may exist in patients with amblyopia [20]. Therefore, it could be concluded that the spherical refraction may obscure the analysis of contrast sensitivity at low spatial frequencies; The interocular comparison suggested that eyes with lower cylindrical refraction tended to show higher CS at high spatial frequencies.…”
Section: Discussionmentioning
confidence: 98%